Anti-icing coating for wind power generation blade as well as preparation method and application of anti-icing coating
By using anti-freezing coating composed of silicone modified fluorocarbon resin and superhydrophobic silica particles on wind power blades, the problem of anti-freezing performance attenuation of existing coatings is solved, achieving longer anti-freezing effect and better weather resistance and UV aging resistance.
Patent Information
- Application Number
- CN202510086242.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2045-01-20
AI Technical Summary
After the existing anti-icing coating is used on wind power blades, the anti-icing performance is rapidly attenuated, resulting in frequent replacement, which increases the cost.
Using an anti-icing coating composed of silicone modified fluorocarbon resin and superhydrophobic silica particles, a superhydrophobic surface is formed by modifying the special micro-nano structure of the resin and nanosilicon dioxide, and the adhesion of the ice layer is reduced.
It significantly extends the anti-icing effect, reduces the adhesion of the ice layer, improves the weather resistance and UV aging resistance of the coating, reduces the frequency of changing the coating, and reduces the cost of use.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of coatings, and in particular to an anti-icing coating for wind power generation blades and a preparation method and application thereof. Background Art
[0002] my country has a vast territory and a complex and changeable climate. There are many types of ice, such as rime, frost / snow, clear ice / rain rime, and mixed ice. In the entire region of my country, except for the southern region, wind turbine blades will suffer from ice damage. Once the blades are frozen, the protection device will automatically shut down, otherwise the blades will be damaged due to the destruction of mass balance, causing damage to the blades and other devices. Therefore, during the icing period, wind turbines will stop operating for a long time, which will seriously affect the power generation efficiency of wind turbines.
[0003] Long-term icing has a huge impact on the power generation income of wind power operators. Manual mechanical deicing requires high-altitude work, which is labor-intensive and has a high risk factor. Hot air deicing requires a large amount of heat, and costs and heating efficiency must be considered. In addition, it is difficult to apply to existing projects. Passive deicing is to reduce the adhesion of ice to the surface of the substrate by coating anti-icing coating on the substrate surface, thereby reducing the ice-forming time of the blades. Its advantages are low cost and easy use.
[0004] At present, the anti-icing coating on the market mainly adopts hydrophobic and anti-fouling coating. Although the initial effect is good, the hydrophobic and anti-fouling properties of this type of coating are mostly obtained by using additives, which leads to serious attenuation of anti-icing performance and usually only one year of anti-icing effect. Wind power generation equipment is generally built on mountains, coastal beaches or places with complex natural environments. In addition, the height of the equipment itself is usually more than 100 meters, and the cost of frequent replacement of coatings is huge. Therefore, there is a special need for an anti-icing coating with a long-term effect. Summary of the invention
[0005] Purpose of the invention: In view of the above technical problems, the present invention proposes an anti-icing coating for wind turbine blades and a preparation method and application thereof.
[0006] The technical solutions adopted are as follows: An anti-icing coating for a wind power blade, comprising component A and component B; The mass ratio of component A to component B is 9-10:1; The component A comprises 42-45wt% of organosilicon-modified fluorocarbon resin, 0.8-1.0wt% of wetting and dispersing agent, 15-20wt% of titanium dioxide, 5-8wt% of superhydrophobic silica particles, 0.3-0.5wt% of rheological additive, 0.8-1wt% of leveling agent, 0.1-0.2wt% of defoamer, 1-1.2wt% of ultraviolet light absorber, 0.8-1wt% of light stabilizer, and the balance is organic solvent I; In the component B, the aliphatic isocyanate curing agent is 65-70wt%, and the balance is the organic solvent II; The preparation method of the organosilicon-modified fluorocarbon resin is as follows: Add fluorocarbon resin and vinyltrimethoxysilane to toluene, stir and mix well, then stir at 60-70°C for 30-60 min, then add organotin catalyst and deionized water, heat to reflux and stir to react for 4-8 hours, then use a water separator to separate the deionized water, return to room temperature, add polymethylhydrogensiloxane and chloroplatinic acid, continue to heat to reflux and stir to react for 10-15 hours, and finally remove the toluene by distillation under reduced pressure.
[0007] Furthermore, the mass ratio of the fluorocarbon resin, vinyltrimethoxysilane and polymethylhydrogensiloxane is 10:1-5:0.1-1.
[0008] Furthermore, the preparation method of the super hydrophobic silica particles is as follows: Add amide silicon powder and acyl chloride nano-silicon dioxide in a mass ratio of 1-5:1-5 into dichloromethane, use triethylamine as an acid-binding agent, reflux for 12-48 hours, centrifuge, collect the product, wash it, and dry it.
[0009] Furthermore, the preparation method of the amino silicon micropowder is as follows: Place silicon micropowder with a particle size of 1-5 μm in a muffle furnace and keep it at 550-600°C for 5-10 hours, then cool it to room temperature, add it to a 5-10 mol / L hydrochloric acid solution, heat it to 60-80°C for activation for 1-5 hours, cool it to room temperature and centrifuge it, collect the precipitate, wash it with deionized water until it is neutral and then dry it to obtain activated silicon micropowder, add the activated silicon micropowder into anhydrous ethanol, ultrasonically disperse it for 10-30 minutes, add 3-aminopropyltriethoxysilane dropwise, heat it to reflux for reaction for 5-10 hours after the dropwise addition, centrifuge it after the reaction is completed, collect the precipitate, wash it with anhydrous ethanol and then dry it.
[0010] Furthermore, the preparation method of the acyl chloride nano silicon dioxide is as follows: Anhydrous ethanol, deionized water and ammonia water are mixed to obtain solution A, tetraethyl orthosilicate is dissolved in anhydrous ethanol to obtain solution B, solution B is slowly added dropwise to solution A, after the addition is completed, the mixture is stirred at 40-60°C for 5-10 hours, and then the mixture is restored to room temperature and allowed to stand, the supernatant is poured out, and the remaining solid is fully washed with anhydrous ethanol to obtain nano-silicon dioxide with a particle size of 10-100 nm, KH-550 and succinic anhydride are dispersed in DMF, and then a DMF suspension of nano-silicon dioxide dispersed by ultrasound is added, and deionized water is added at the same time, and the mixture is stirred at 40-60°C for 5-10 hours, and then centrifuged, the precipitate is collected and fully washed with anhydrous ethanol to obtain carboxylated nano-silicon dioxide, the carboxylated nano-silicon dioxide is dispersed in dichloromethane, thionyl chloride is added dropwise, and the mixture is heated to reflux for 1-10 hours, centrifuged, and the precipitate is collected and dried.
[0011] Further, the organic solvent I is propylene glycol methyl ether acetate and / or butyl acetate; The organic solvent II is propylene glycol methyl ether acetate and / or butyl acetate.
[0012] The present invention also provides a method for preparing an anti-icing coating for a wind turbine blade, which is as follows: The organosilicon-modified fluorocarbon resin, wetting and dispersing agent, titanium dioxide, rheological additive, leveling agent, defoamer, ultraviolet light absorber, light stabilizer and organic solvent I are mixed and ground for 30-60 minutes, and then super-hydrophobic silica particles are added and ground for 1-10 minutes to obtain component A; Adding an aliphatic isocyanate curing agent into an organic solvent II and mixing well to obtain component B; Stir component A and component B thoroughly until they are mixed.
[0013] The present invention also provides application of the anti-icing coating for wind power generation blades in the anti-icing field.
[0014] Beneficial effects of the present invention: The present invention provides an anti-icing coating for wind turbine blades. The organic silicon modified fluorocarbon resin used in the present invention has certain hydrophobicity and excellent weather resistance, and can provide a longer anti-icing effect. Vinyl trimethoxysilane will undergo a hydrolysis reaction under the condition of a catalyst when it meets water to generate Si-OH. Si-OH will undergo a dehydration or dealcoholization condensation reaction with each other or with Si-O-CH3 to form a cross-linked structure. At the same time, Si-OH and Si-O-CH3 will also react with -OH and -COOH in the fluorocarbon resin. The double bonds in vinyl trimethoxysilane react with polymethyl hydrogen siloxane under the catalysis of chloroplatinic acid to form a silylation reaction, thus connecting the long chain of polysiloxane with the fluorocarbon resin. Polysiloxane is not only hydrophobic, but also has good resistance to environmental factors such as ultraviolet rays, thus improving the anti-ultraviolet aging ability of the coating. The special micro-nano structure formed by the amino silicon micropowder and the acyl chloride nano-silicon dioxide connected by chemical bonds in the present invention can show higher roughness, and the formed super-hydrophobic surface can reduce the adhesion between the ice layer and the coating, which is conducive to the shedding of the ice layer, improves the anti-icing property of the coating, and has better stability. In addition, based on the shielding effect of the super-hydrophobic silica particles against ultraviolet rays, the coating of the present invention has better anti-ultraviolet aging performance.
[0015] The coating formed by the anti-icing coating prepared by the present invention has a super-hydrophobic surface, which can not only provide a waterproof and self-cleaning effect, but also achieve an anti-icing effect by reducing the contact area of the solid-liquid interface, prolonging the freezing time and reducing ice adhesion. It also has good weather resistance, does not require frequent replacement of the coating, and reduces the cost of use. DETAILED DESCRIPTION
[0016] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially. The techniques not mentioned in the present invention are all referenced to the prior art. Unless otherwise specified, the following examples and comparative examples are parallel experiments, using the same processing steps and parameters.
[0017] Embodiment 1: An anti-icing coating for a wind power blade, comprising a component A and a component B in a mass ratio of 9:1; Silicone-modified fluorocarbon resin in component A: 43wt%; The wetting and dispersing agent is BYK2025: 1.0wt%; Titanium dioxide is DuPont Ti-Pure R-960: 15wt%; Super hydrophobic silica particles: 5wt%; The rheological additive is Arkema crayvallac super: 0.4wt%; Leveling agent is BKY355: 0.8wt%; The defoamer is AC-300 from Japan Kyoeisha: 0.15wt%; The UV absorber is BASF Tinuvin 1130: 1.2wt%; Light stabilizer: BASF Tinuvin 123: 0.8wt%; The balance is propylene glycol methyl ether acetate and butyl acetate in a mass ratio of 1:1; In component B, the aliphatic isocyanate curing agent Wanhua HT-100 is 68wt%, and the balance is propylene glycol methyl ether acetate.
[0018] The preparation method of the organosilicon-modified fluorocarbon resin is as follows: Add 100g of fluorocarbon resin and 40g of vinyltrimethoxysilane to 1000ml of toluene, stir and mix, then heat to 60℃ and stir for 30min, then add 0.5g of dibutyltin dilaurate and 10ml of deionized water, heat to reflux and stir for 6h, then use a water separator to separate the deionized water, return to room temperature, add 5g of polymethylhydrogensiloxane and 0.001g of chloroplatinic acid, continue to heat to reflux and stir for 10h, and finally remove the toluene by distillation under reduced pressure.
[0019] The preparation method of super hydrophobic silica particles is as follows: The silicon micropowder with a particle size of 1-5 μm was placed in a muffle furnace at 600 ° C for 5 hours and then cooled to room temperature. Then, it was added to 8 mol / L hydrochloric acid solution at a solid-liquid mass ratio of 1:10, heated to 70 ° C for activation for 2 hours, cooled to room temperature and centrifuged, the precipitate was collected, washed with deionized water until neutral, and then dried to obtain activated silicon micropowder. 40 g of activated silicon micropowder was added to 500 ml of anhydrous ethanol, ultrasonically dispersed for 30 minutes, and 1.5 g of 3-aminopropyltriethoxysilane, after the dripping is completed, the temperature is raised to reflux for reaction for 8h, after the reaction is completed, centrifuge, collect the precipitate, wash it thoroughly with anhydrous ethanol, and then dry it to obtain amino silicon powder, mix 400ml anhydrous ethanol, 75ml deionized water and 25ml ammonia water to obtain solution A, dissolve 25ml ethyl orthosilicate in 50ml anhydrous ethanol to obtain solution B, slowly add solution B to solution A, stir and react at 60℃ for 8h after the dripping is completed, then return to room temperature and stand, pour out the supernatant, wash the remaining solid with anhydrous ethanol to obtain nano-silica with a particle size of 10-100nm, take 5g of the above nano-silica, add it to 50ml DMF and ultrasonically disperse it for 30min to obtain a suspension, disperse 2.2g KH-550 and 1g succinic anhydride in 10ml DMF, and then drop it into the suspension, add 1 ml of deionized water at the same time, stir and react at 60 ° C for 8 hours, then centrifuge, collect the precipitate and wash it with anhydrous ethanol to obtain carboxylated nano-silica, disperse the carboxylated nano-silica in 100 ml of dichloromethane, add 10 ml of dichlorothionyl, heat to reflux for 5 hours, centrifuge, collect the precipitate and dry it to obtain acyl chloride nano-silica, add amino silicon micropowder and acyl chloride nano-silica in a mass ratio of 1:1 to sufficient dichloromethane, use an appropriate amount of triethylamine as an acid binding agent, reflux for 24 hours, centrifuge, collect the product, wash it with anhydrous ethanol, and dry it.
[0020] The preparation method of the above-mentioned anti-icing coating for wind turbine blades is as follows: The organosilicon-modified fluorocarbon resin, wetting and dispersing agent, titanium dioxide, rheological additive, leveling agent, defoamer, ultraviolet light absorber, light stabilizer, propylene glycol methyl ether acetate and butyl acetate were mixed and ground for 40 minutes, and then super-hydrophobic silica particles were added and continued to grind for 5 minutes to obtain component A. The aliphatic isocyanate curing agent was added to the propylene glycol methyl ether acetate and mixed to obtain component B. Component A and component B were fully stirred to mix.
[0021] Embodiment 2: An anti-icing coating for a wind power blade, comprising a component A and a component B in a mass ratio of 9:1; Silicone-modified fluorocarbon resin in component A: 45wt%; The wetting and dispersing agent is BYK2025: 1.0wt%; Titanium dioxide is DuPont Ti-Pure R-960: 18wt%; Super hydrophobic silica particles: 6wt%; Rheological additive: Arkema crayvallac super: 0.5wt%; Leveling agent is BKY355: 1wt%; The defoamer is AC-300 from Japan Kyoeisha: 0.2wt%; The UV absorber is BASF Tinuvin 1130: 1.2wt%; Light stabilizer is BASF Tinuvin 123: 1wt%; The balance is propylene glycol methyl ether acetate and butyl acetate in a mass ratio of 1:1; The aliphatic isocyanate curing agent in component B is Wanhua HT-100: 70wt%, and the balance is propylene glycol methyl ether acetate.
[0022] Wherein, the preparation method of organosilicon-modified fluorocarbon resin and super-hydrophobic silica particles is the same as that of Example 1; The preparation method of the above-mentioned anti-icing coating for wind turbine blades is as follows: The organosilicon-modified fluorocarbon resin, wetting and dispersing agent, titanium dioxide, rheological additive, leveling agent, defoamer, ultraviolet light absorber, light stabilizer, propylene glycol methyl ether acetate and butyl acetate were mixed and ground for 40 minutes, and then super-hydrophobic silica particles were added and continued to grind for 5 minutes to obtain component A. The aliphatic isocyanate curing agent was added to the propylene glycol methyl ether acetate and mixed to obtain component B. Component A and component B were fully stirred to mix.
[0023] Embodiment 3: An anti-icing coating for a wind power blade, comprising a component A and a component B in a mass ratio of 9:1; Silicone-modified fluorocarbon resin in component A: 42wt%; The wetting and dispersing agent is BYK2025: 0.8wt%; Titanium dioxide is DuPont Ti-Pure R-960: 18wt%; Super hydrophobic silica particles: 8wt%; Rheological additive: Arkema crayvallac super: 0.3wt%; Leveling agent is BKY355: 0.8wt%; The defoamer is AC-300 from Japan Kyoeisha: 0.1wt%; The UV absorber is BASF Tinuvin 1130: 1wt%; Light stabilizer: BASF Tinuvin 123: 0.8wt%; The balance is propylene glycol methyl ether acetate and butyl acetate in a mass ratio of 1:1; The aliphatic isocyanate curing agent in component B is Wanhua HT-100: 65wt%, and the balance is propylene glycol methyl ether acetate.
[0024] Wherein, the preparation method of organosilicon-modified fluorocarbon resin and super-hydrophobic silica particles is the same as that of Example 1; The preparation method of the above-mentioned anti-icing coating for wind turbine blades is as follows: The organosilicon-modified fluorocarbon resin, wetting and dispersing agent, titanium dioxide, rheological additive, leveling agent, defoamer, ultraviolet light absorber, light stabilizer, propylene glycol methyl ether acetate and butyl acetate were mixed and ground for 40 minutes, and then super-hydrophobic silica particles were added and continued to grind for 5 minutes to obtain component A. The aliphatic isocyanate curing agent was added to the propylene glycol methyl ether acetate and mixed to obtain component B. Component A and component B were fully stirred to mix.
[0025] Comparative Example 1: The method is basically the same as Example 1, except that commercially available nano-silica (Tianxing New Material TSP-L12) is used instead of super-hydrophobic silica particles.
[0026] Comparative Example 2: The method is basically the same as Example 1, except that the fluorocarbon resin is not modified by polymethylhydrogensiloxane; The preparation method of fluorocarbon resin is as follows: Add 100g of fluorocarbon resin and 40g of vinyltrimethoxysilane into 1000ml of toluene, stir and mix, then heat to 60°C and stir for 30min. Then add 0.5g of dibutyltin dilaurate and 10ml of deionized water, heat to reflux and stir for 6h, then remove the small molecule solvent by distillation under reduced pressure.
[0027] Comparative Example 3: It is basically the same as Example 1, except that the fluorocarbon resin is directly added, that is, the fluorocarbon resin is not modified.
[0028] Performance Test: The glass slide was repeatedly washed with deionized water and anhydrous ethanol for several times and dried in a drying oven. The anti-icing coatings prepared in Examples 1-3 of the present invention and Comparative Examples 1-3 and commercially available anti-icing coatings (COSCO Kansai and Dalian Yibang) were sprayed onto the surface of the glass slide with a nozzle about 15-20 cm away from the substrate, and then the glass slide was placed in a drying oven at 60° C. for 24 h to obtain a coating.
[0029] The static contact angle of the droplet on the coating surface was measured using the SDC-100 optical contact angle meter by the sessile drop method, and the rolling angle of the droplet just rolling down the coating surface was measured using the GFSG60-35 manual angle stage.
[0030] The UV-1140 ultraviolet accelerated weathering test chamber is used to simulate the aging effect of ultraviolet rays in sunlight on the coating. The test chamber uses a UVA-340 fluorescent ultraviolet lamp as the ultraviolet light source, and the irradiation intensity is 0.68W / m 2 (340nm), which is equivalent to the average sunlight intensity at noon in summer at the equator. According to the UV aging test standard, when the test chamber is at an operating temperature of 61-70℃, 12h of indoor UV radiation is equivalent to 30d of outdoor UV radiation. Therefore, the test temperature is controlled at (65.5±1)℃, the aging time is set to 288h, and the static contact angle and rolling angle are measured. The test results are shown in Table 1 below: ; It can be seen from Table 1 above that the coating formed by the anti-icing coating prepared by the present invention has a super-hydrophobic surface, which can not only provide a waterproof and self-cleaning effect but also achieve an anti-icing effect by reducing the contact area of the solid-liquid interface, prolonging the freezing time and reducing ice adhesion.
[0031] From the comparison between Example 1 and Comparative Example 1, it can be seen that the super-hydrophobic silica particles prepared by the present invention play a positive role in improving the static contact angle of the coating and reducing the rolling angle, and also have a certain contribution to improving the anti-ultraviolet aging performance; From the comparison between Example 1 and Comparative Examples 2 and 3, it can be seen that the organosilicon-modified fluorocarbon resin prepared by the present invention plays a positive role in improving the static contact angle of the coating and reducing the rolling angle, and also has a certain contribution to improving the anti-ultraviolet aging performance; Moreover, by comparing with commercially available anti-icing coatings, it can be seen that the anti-icing performance and anti-ultraviolet aging performance of the anti-icing coating of the present invention are both superior.
[0032] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. An anti-icing coating for wind turbine blades, characterized in that: Comprising component A and component B; The mass ratio of component A to component B is 9-10:1; The component A comprises 42-45wt% of organosilicon-modified fluorocarbon resin, 0.8-1.0wt% of wetting and dispersing agent, 15-20wt% of titanium dioxide, 5-8wt% of superhydrophobic silica particles, 0.3-0.5wt% of rheological additive, 0.8-1wt% of leveling agent, 0.1-0.2wt% of defoamer, 1-1.2wt% of ultraviolet light absorber, 0.8-1wt% of light stabilizer, and the balance is organic solvent I; In the component B, the aliphatic isocyanate curing agent is 65-70wt%, and the balance is the organic solvent II; The preparation method of the organosilicon-modified fluorocarbon resin is as follows: Add fluorocarbon resin and vinyltrimethoxysilane to toluene, stir and mix well, then stir at 60-70°C for 30-60 min, then add organotin catalyst and deionized water, heat to reflux and stir to react for 4-8 hours, then use a water separator to separate the deionized water, return to room temperature, add polymethylhydrogensiloxane and chloroplatinic acid, continue to heat to reflux and stir to react for 10-15 hours, and finally remove the toluene by distillation under reduced pressure.
2. The anti-icing coating for wind turbine blades according to claim 1, characterized in that: The mass ratio of the fluorocarbon resin, vinyl trimethoxy silane and polymethyl hydrogen siloxane is 10:1-5:0.1-1.
3. The anti-icing coating for wind turbine blades according to claim 1, characterized in that: The preparation method of the super hydrophobic silica particles is as follows: Add amide silicon powder and acyl chloride nano-silicon dioxide in a mass ratio of 1-5:1-5 into dichloromethane, use triethylamine as an acid-binding agent, reflux for 12-48 hours, centrifuge, collect the product, wash it, and dry it.
4. The anti-icing coating for wind turbine blades according to claim 3, characterized in that: The preparation method of the amino silicon micropowder is as follows: Place silicon micropowder with a particle size of 1-5 μm in a muffle furnace and keep it at 550-600°C for 5-10 hours, then cool it to room temperature, add it to a 5-10 mol / L hydrochloric acid solution, heat it to 60-80°C for activation for 1-5 hours, cool it to room temperature and centrifuge it, collect the precipitate, wash it with deionized water until it is neutral and then dry it to obtain activated silicon micropowder, add the activated silicon micropowder into anhydrous ethanol, ultrasonically disperse it for 10-30 minutes, add 3-aminopropyltriethoxysilane dropwise, heat it to reflux for reaction for 5-10 hours after the dropwise addition, centrifuge it after the reaction is completed, collect the precipitate, wash it with anhydrous ethanol and then dry it.
5. The anti-icing coating for wind turbine blades according to claim 3, characterized in that: The preparation method of the acyl chloride nano silicon dioxide is as follows: Anhydrous ethanol, deionized water and ammonia water are mixed to obtain solution A, tetraethyl orthosilicate is dissolved in anhydrous ethanol to obtain solution B, solution B is slowly added dropwise to solution A, after the addition is completed, the mixture is stirred at 40-60°C for 5-10 hours, and then the mixture is restored to room temperature and allowed to stand, the supernatant is poured out, and the remaining solid is fully washed with anhydrous ethanol to obtain nano-silicon dioxide with a particle size of 10-100 nm, KH-550 and succinic anhydride are dispersed in DMF, and then a DMF suspension of nano-silicon dioxide dispersed by ultrasound is added, and deionized water is added at the same time, and the mixture is stirred at 40-60°C for 5-10 hours, and then centrifuged, the precipitate is collected and fully washed with anhydrous ethanol to obtain carboxylated nano-silicon dioxide, the carboxylated nano-silicon dioxide is dispersed in dichloromethane, thionyl chloride is added dropwise, and the mixture is heated to reflux for 1-10 hours, centrifuged, and the precipitate is collected and dried.
6. The anti-icing coating for wind turbine blades according to claim 1, characterized in that: The organic solvent I is propylene glycol methyl ether acetate and / or butyl acetate; The organic solvent II is propylene glycol methyl ether acetate and / or butyl acetate.
7. A method for preparing an anti-icing coating for a wind turbine blade according to any one of claims 1 to 6, characterized in that: The details are as follows: The organosilicon-modified fluorocarbon resin, wetting and dispersing agent, titanium dioxide, rheological additive, leveling agent, defoamer, ultraviolet light absorber, light stabilizer and organic solvent I are mixed and ground for 30-60 minutes, and then super-hydrophobic silica particles are added and ground for 1-10 minutes to obtain component A; Adding an aliphatic isocyanate curing agent into an organic solvent II and mixing well to obtain component B; Stir component A and component B thoroughly until they are mixed.
8. Use of the anti-icing coating for wind turbine blades according to any one of claims 1 to 6 in the anti-icing field.
Citation Information
Patent Citations
Polymer ice-coating-preventing coating containing modified nano particles and preparing method thereof
CN103483890A
Frost prevention coating and preparation method and application thereof
CN104530975A
Anti-ultraviolet super-hydrophobic fluorosilicone coating as well as preparation method and application thereof
CN114854311A
Anti-icing coating for offshore oilfield facilities and equipment
CN116716001A
Fastener friction-resistant self-drying fluorosilicone coating material and preparation method thereof
CN117327449A